Giant microwave absorption in fine powders of superconductors - Csősz, G.; Márkus, B. G.; Jánossy, A.; Nemes, N. M.; Murányi, F.; Klupp, G.; Kamarás, K.; Kogan, V. G.; Bud’ko, S. L.; Canfield, P. C.; Simon, F. (Scientific reports, 2018)
Enhanced microwave absorption, larger than that in the normal state, is observed in fine grains of type-II superconductors (MgB 2 and K 3 C 60 ) for magnetic fields as small as a few % of the upper critical field. The effect is predicted by the theory of vortex motion in type-II superconductors, however its direct observation has been elusive due to skin-depth limitations; conventional microwave absorption studies employ larger samples where the microwave magnetic field exclusion significantly lowers the absorption. We show that the enhancement is observable in grains smaller than the penetration depth. A quantitative analysis on K 3 C 60 in the framework of the Coffey–Clem (CC) theory explains well the temperature dependence of the microwave absorption and also allows to determine the vortex pinning force constant.